Utilizing robotic total station technology for landslide risk mitigation in urban development - Zainon, Othman; Mohd Radzi, Mohamad Taqiff (Faculty of Civil Engineering, 2025)
In Malaysia, landslides have resulted in significant damage to infrastructure and fatalities, highlighting the need for precise and continuous monitoring systems. Landslides are a critical geotechnical hazard that pose significant risks to urban development. Traditional slope monitoring methods, such as manual surveying and satellite-based remote sensing, often lack real-time capabilities and the accuracy required for early warning systems. To address these limitations, this study investigates the application of Robotic Total Station (RTS) technology in landslide risk mitigation. Assessing RTS's ability to accurately identify and analyse slope variations is the main goal of this study. The study was carried out in the landslide-prone region of Sireh Park, Iskandar Puteri, Johor Bahru, where two control stations and a network of thirteen monitoring points were set up. Geospatial displacement data was gathered over two epochs using a Topcon RTS GT-1001; measurements were processed using Magnet Field software. The findings showed different levels of slope deformation; MP9 showed the most displacement with 0.449 m, suggesting localized instability, while MP13 showed the least amount of movement with 0.007 m. These results validate that RTS offers high-precision, real-time monitoring, greatly enhancing early detection and response tactics for urban projects at risk of landslides. RTS is a useful tool for geotechnical risk assessment since it provides automated data gathering, lowers operating costs, and improves accuracy when compared to conventional geodetic methods. In conclusion, urban resilience against landslide risks may be greatly increased by combining RTS with early warning systems and predictive Geographical Information System modelling.